Cannabidiol Prevents Motor and Cognitive Impairments Induced by Reserpine in Rats - Peres, Fernanda F.; Levin, Raquel; Suiama, Mayra A.; Diana, Mariana C.; Gouvêa, Douglas A.; Almeida, Valéria; Santos, Camila M.; Lungato, Lisandro; Zuardi, Antônio W.; Hallak, Jaime E. C.; Crippa, José A.; Vânia, D’Almeida; et al. (Frontiers in Pharmacology, 2016)
Cannabidiol (CBD) is a non-psychotomimetic compound from Cannabis sativa that presents antipsychotic, anxiolytic, anti-inflammatory, and neuroprotective effects. In Parkinson’s disease patients, CBD is able to attenuate the psychotic symptoms induced by L-DOPA and to improve quality of life. Repeated administration of reserpine in rodents induces motor impairments that are accompanied by cognitive deficits, and has been applied to model both tardive dyskinesia and Parkinson’s disease. The present study investigated whether CBD administration would attenuate reserpine-induced motor and cognitive impairments in rats. Male Wistar rats received four injections of CBD (0.5 or 5 mg/kg) or vehicle (days 2–5). On days 3 and 5, animals received also one injection of 1 mg/kg reserpine or vehicle. Locomotor activity, vacuous chewing movements, and catalepsy were assessed from day 1 to day 7. On days 8 and 9, we evaluated animals’ performance on the plus-maze discriminative avoidance task, for learning/memory assessment. CBD (0.5 and 5 mg/kg) attenuated the increase in catalepsy behavior and in oral movements – but not the decrease in locomotion – induced by reserpine. CBD (0.5 mg/kg) also ameliorated the reserpine-induced memory deficit in the discriminative avoidance task. Our data show that CBD is able to attenuate motor and cognitive impairments induced by reserpine, suggesting the use of this compound in the pharmacotherapy of Parkinson’s disease and tardive dyskinesia.